Assessing the organizational performance of the Indonesian Midwife Association - Kurnia, Ike; Ayuningtyas, Dumilah (BKM Public Health and Community Medicine, 2024)
Purpose: This research aims to determine the performance of the Indonesian Midwives Association, especially for the central region, including provincial and branch levels, following the International Confederation of Midwives Global Standards. Methods: The rapid survey method was conducted from November to December 2023. The self-assessment is carried out using an instrument developed in 2020, an adaptation of the Member Association Capacity Assessment Tool (MACAT). MACAT consists of 7 sections, 15 components, and 68 statements. Various levels of the Indonesia Midwives Association at provincial and branch levels, including the central region, complete the assessment. Organizational performance assessment is based on management level, system approach indicators, and 15 components. Results: The IBI district management in each province in the central region mostly has a percentage of above-average organizational performance achievements. Central Sulawesi has the highest performance percentage, while Gorontalo province has the lowest rate of organizational performance. Organizational performance is based on the system approach indicators; 3 out of 4 indicators are above average, and the outcome is the lowest. The distribution of the performance assessment of the PC IBI management organization in each province according to the system approach indicators showed that the results were mostly above standard. The organizational performance assessment based on the overall system approach indicators shows that Central Sulawesi Province is in the highest position, while NTT is in the lowest position. Based on the achievement of all components of organizational performance, South Kalimantan has the highest achievement, while NTT has the lowest achievement. Among 15 components of organizational performance assessment five components are below average (sustainability, communication, impact of policy advocacy, infrastructure & information systems, and finance). Conclusion: In general, 12 provinces in the central region received ratings above the standard based on average. Provinces whose scores are below standard are expected to make improvements based on the evaluation and feedback provided. The results of the organizational performance assessment can be formulated into strategic recommendations for the future development of the IBI organization.